Ordering kinetics evaluation of FeAl powders. (December 2017) - Cinca, N.; Isalgué, A.; Auguet, C.; Concustell, A.; Cano, I.G.; Guilemany, J.M.; Fauth, F.
Abstract: In this study, time resolved X-ray diffraction experiments using synchrotron X-ray radiation have been performed to get insight on the time and temperature dependent atomic ordering of an intermetallic Fe-40Al (at.%) ball-milled powder. The target of the present study is to gain knowledge on the rapid heating processes occurring during Thermal Spray coating processes. Present results show that in the temperature range 400 °C - 550 °C, the evolution of the order can be followed and modelled by fitting the powder diffraction patterns collected within the first minutes after fast heating. Reasonable refinements have been obtained by assuming the presence of two domains corresponding to the ordered and disordered lattices. The lattice constant changes from 0.29165 nm in the ball-milled powder at room temperature to 0.29281 nm in the ordered phase after 3000 s at 550 °C. The growth of the ordered phase is proposed to be a vacancy-related process with an activation energy of 1.04 eV. Above 550 °C, the ordering kinetics appears too fast to be resolved using the few seconds time scale of the present experiments which is in agreement to thermal spray results conditions. Highlights: Ordering of the intermetallic Fe40 at%Al structure upon heating at different temperatures. Use of the synchrotron radiation for the time-resolved evaluation. Rietveld analysis for the evolution of fitting parameters to check strain tendency and growth of ordered domains.